Analysis of Achievement of Islamic-Entrepreneurial Science and Technology (I-EnSciT) Module Training for Prospective Indonesian-Malaysian Science Teachers - Rian Vebrianto; Ridzwan Che Rus; Radeswandri Radeswandri; Misbahul Jannah; Irfan Andi Gafur (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
This study aims to determine the response to the Islamic-Entrepreneurial Science and Technology (I-EnSciT) module for prospective science teachers in Indonesia and Malaysia. This research is an applied research type of evaluation with a cross-sectional method in the form of a reflection questionnaire which includes material aspects, Delivery, and Response Strategy to find out the response of prospective science teachers to the I-EnSciT Module training program. Data is obtained by conducting training activities within a certain period, then an assessment of the training program is carried out through a Google form questionnaire that is packaged to make it easier for participants to fill out a reflection questionnaire. This research was conducted with a total of 250 respondents, including 175 prospective teachers in Indonesia and 75 prospective teachers in Malaysia. Data analysis was carried out descriptively and inference was carried out using SPSS V21. Based on the results of the study, it was shown that the average recapitulation of reflection on material aspects, strategies, and responses obtained a value of 3.3 with the aspect category